Evaluation of echocardiographic systolic parameters in pre eclamptics and normotensives women - Jain, Neha; Verma, Asha; Jain, Shikha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Early detection of changes in cardiovascular echocardiographic systolic parameters and their comparison with normotensives women. Methods: This was a hospital based prospective case control study carried out in department of obstetrics and gynaecology in S.M.S Medical College, Jaipur during the period from February 2013 to December 2014. 100 women were enrolled in the study after applying inclusion and exclusion criteria. All women underwent two dimensional echocardiography at rest. Cardiac systolic parameters were recorded and studied. Results: Mean LVEDV in PIH group was 75.71 ± 4.8 ml v/s 71.08 ± 5.6 ml in control group and the difference was statistically significant. Mean stroke volume was higher in PIH group as compared to the control group and the difference was statistically significant (59.83 ± 7.4ml/min v/s 52.48 ± 6.4ml/min). Mean Aortic Root Diameter in PIH group was 2.188 ± 1.04 cm as compared to the 1.866 ± 1.06 cm in the control group which was statistically significant. Mean Left Ventricular outflow Tract diameter was slightly higher in the PIH group as compared to the controls although the P-value was not significant (2.37 ± 1.06 cm and 1.99 ± 1.08 cm). Mean Total Vascular Resistance in PIH group was found to be higher in PIH group as compared to the controls and the difference was statistically significant (1389 ± 57.04 dynes/sec/cm-5 v/s 1286 ± 45.01 dynes/sec/cm-5). Conclusions: Systolic parameters get worsened in pre eclamptics. Early detection of change in these parameters could help to identify high risk women who are prone to develop cardiovascular morbidity in later life.